Principles of biochemistry with a human focus - Garrett, Reginald H. (Harcourt College Publishers, 1997)
PRINCIPLES OF BIOCHEMISTRY WITH A HUMAN FOCUS provides pre-med, junior, and senior science majors the most up-to-date coverage of biochemistry and a distinct focus on the topics most relevant to human health and medicine. Written by a chemist (Grisham) and a biologist (Garrett), the book presents biochemistry from a balanced perspective. PRINCIPLES OF BIOCHEMISTRY stresses the principles governing structure, function, and interactions of biological molecules.